Development Of Health And Safety Management System Based On Collaborative Robots - Ony Patricia (IC-ITECHS, 2022)
The era of the society 5.0 is a concept that defines technology and people to improve the quality of human life in a sustainable manner. One of these technological advances is Society 5.0, which was initiated by the Japanese. This concept allows us to use modern science-based such as Internet Of Things (IoT), Artificial Intelligence (AI) and Robots for human needs in order to live comfortably and more effectively. This article aims to create a strategy for expanding the characteristics of occupational safety and health in the era of the society 5.0. This strategy creates new technologies to make it easier for humans to do industrial work that focuses on the safety and health of employees in the workplace from accidents and exposure to hazardous substances. One of the technologies used in society 5.0 is Cobots, which is designed to make programming simple through a Human-Machine Interface (HMI). The use of cobots also enables companies to achieve a faster Return on Investment (RoI) as it provides rest time for workers and allows them to handle higher productivity processes and ultimately acquire new skills. So that this concept will make management and strategies more effective, efficient, and innovative, in creating high worker performance so that it can support the success and improvement of the company's quality to protect workers from accidents and occupational safety and health in the era of society 5.0.